AdipoCount: A New Software for Automatic Adipocyte Counting - Zhi, Xuhao; Wang, Jiqiu; Lu, Peng; Jia, Jue; Shen, Hong-Bin; Ning, Guang (Frontiers in Physiology, 2018)
Obesity has spread worldwide and become a common health problem in modern society. One typical feature of obesity is the excessive accumulation of fat in adipocytes, which occurs through the following two physiological phenomena: hyperplasia (increase in quantity) and hypertrophy (increase in size) of adipocytes. In clinical and scientific research, the accurate quantification of the number and diameter of adipocytes is necessary for assessing obesity. In this study, we present a new automatic adipocyte counting system, AdipoCount, which is based on image processing algorithms. Comparing with other existing adipocyte counting tools, AdipoCount is more accurate and supports further manual correction. AdipoCount counts adipose cells by the following three-step process: 1) It detects the image edges, which are used to segment the membrane of adipose cells; 2) It uses a watershed-based algorithm to re-segment the missing dyed membrane; and 3) It applies a domain connectivity analysis to count the cells. The outputs of this system are the labels and the statistical data of all adipose cells in the image. The AdipoCount software is freely available for academic use at: http://www.csbio.sjtu.edu.cn/bioinf/AdipoCount/.